2019
DOI: 10.1089/lap.2018.0360
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Failed Transcystic Laparoscopic Common Bile Duct Exploration: Analysis of Multicenter Integrated Health System Database

Abstract: LCBDE is an effective and safe mean of clearing common bile duct stones at community hospitals of an integrated health system. Previously cited contraindications for TLCBDE are not absolute, but rather predictors of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 15 publications
4
17
1
Order By: Relevance
“…Some studies have demonstrated that elevated bilirubin was associated with failure of CBD exploration, whereas others showed no significance of elevated bilirubin in predicting failure of the operation. 3,11,13 In this study, there was a similar proportion of patients who had an elevated preoperative bilirubin, 52.7% in patients with an unsuccessful LCBDE and 54% in patients with a successful LCBDE. Hence, these results suggest that even without preoperative ERCP and biliary decompression, LCBDE is an effective method of treating choledocholithiasis with high bilirubin level.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Some studies have demonstrated that elevated bilirubin was associated with failure of CBD exploration, whereas others showed no significance of elevated bilirubin in predicting failure of the operation. 3,11,13 In this study, there was a similar proportion of patients who had an elevated preoperative bilirubin, 52.7% in patients with an unsuccessful LCBDE and 54% in patients with a successful LCBDE. Hence, these results suggest that even without preoperative ERCP and biliary decompression, LCBDE is an effective method of treating choledocholithiasis with high bilirubin level.…”
Section: Discussionsupporting
confidence: 61%
“…The relationship between number of CBD stones and the outcome of CBD exploration has been minimally explored in the literature and no association with success has previously been found. 3,13,19,20 Interestingly, despite the higher success rate, multiple stones were found to be associated with an increased risk of serious (Clavien-Dindo 3 or 4) complications in this study (OR: 3.79, 95% CI: 1.66-8.67, P = 0.002, Table 4). Negative outcomes have also been reported in the literature with multiple CBD stones found to be an independent risk factor for conversion to open access.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The rationale behind choosing ERCP over TCBDE is not clearly documented for the other patients. It may be influenced by the positive and negative predictors of TCBDE success as described above, but a prospective analysis of the decision‐making process is warranted to further understand the complexity behind approach selection 18,19 …”
Section: Discussionmentioning
confidence: 99%